Improving students understanding with teaching materials based on augmented reality video animation - Sugiri, Wiku Aji; Wibowo, Agus Mukti; Priatmoko, Sigit; Wijayanto, Adi (Universitas Ahmad Dahlan, 2023)
In the contemporary era marked by profound societal shifts influenced by technology, the increasing integration of digital devices into educational settings necessitates a closer examination of educators' proficiency in leveraging these resources. Despite the availability of state-of-the-art learning facilities at SDN Bunulrejo 1 Malang, the limited optimization of digital tools by teachers presents a critical gap. In contrast, students exhibit a proclivity towards enhanced learning experiences facilitated by digital devices. This study endeavors to elucidate the outcomes of research and development pertaining to augmented reality video animation (ARVA) instructional materials, a mobile-based digital teaching resource. Adhering to the Lee and Owen model encompassing assessment/analysis, design, development, implementation, and evaluation phases, this research engages 18 fourth-grade students and two expert validators (design and material experts). The design expert validation yielded a commendable score of 109 (72.6%), indicative of adequacy, while material expert validation attained a score of 103 (68.6%), similarly meeting adequacy standards. Subsequently, post-implementation, students' average learning outcomes, with a mean score of 75.27, demonstrated a commendable understanding of materials science concepts, qualifying as